High-Intensity Interval Training with Cycling and Calisthenics: Effects on Aerobic Endurance, Critical Power, Sprint and Maximal Strength Performance in Sedentary Males - Murat Kul; Mutlu Turkmen; Umit Yildirim; Ramazan Ceylan; Onur Sipal; Refik Çabuk; Abdullah Akova; Omer Faruk Aksoy; Eda Adatepe (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
TABATA protocol is considered to be one of the most effective strategies among high-intensity interval training (HIIT) methods. A limited number of studies have compared the chronic effects of cycling-based and calistenic HIIT in TABATA-type. The aim of this study was to compare the chronic effects of a 8-week TABATA-type calisthenic high-intensity interval and high-intensity interval in cycling on aerobic endurance, sprint and maximal strength performance in sedentary men. 17 sedentary males participated in our study. Participants were randomly divided into calisthenic HIIT (n=9) and cycling HIIT (n=8) groups. Training groups were given 3-sessions of exercise per week on non-consecutive days for 8 weeks. Before and after the 8-week training, the body mass, body mass index, fat percentage, 30-m sprint, 1-repetition maximal strength, aerobic power and critical power levels of the participants were determined. No statistically significant different was observed in body mass (p=0.917), body mass index (p=0.928), and body fat ratio (p=0.980) in both training groups. However, both training groups achieved statistically significant improvements in peak power output (p=0.017), maximal oxygen consumption (p=0.040) and critical power (p=0.048), and there was no significant difference in the level of improvement between the groups (p>0.05). There was no statistically significant difference in 1 repetition maximal strength and sprint values of both training groups (p<0.05). TABATA type HIIT performed calistenic provides chronic effects similar to that of interval cycling form.